Hydrogen Peroxide Electrogeneration by Gas Diffusion Electrode Modified with Tungsten Oxide Nanoparticles for Degradation of Orange II and Sunset Yellow FCF Azo Dyes - Paz, Edson C.; Pinheiro, Victor S.; Aveiro, Luci R.; Souza, Fernanda L.; Lanza, Marcos R. [UNESP]; Santos, Mauro G. (Soc Brasileira Quimica, 2019)
In this work, the gas diffusion electrode (GDE) cathode of Vulcan XC72 carbon modified with nanoparticles of WO2.72 (WO2.72 / Vulcan XC72) was used for H2O2 electrogeneration and degradation of 350 mL of Orange II (OH) and Sunset Yellow FCF (SY) azo dyes by electro-Fenton (EF) and photoelectro-Fenton (PEF) processes with different Fe2+ initial content (1.00, 0.50 and 0.25 mmol L-1). The WO2.72 / Vulcan XC72 GDE electrolyzed approximately 3 times more H2O2 than the Vulcan XC72 GDE. Decolorizations and mineralizations of the dye solutions were more efficient at higher concentrations of Fe2+. The decolorization decay showed pseudo-first-order kinetics. The most promising decolorization results obtained at processes of WO2.72 / Vulcan XC72 cathode combined with Pt anode (100% color removal of OII and SY at 30 and 20 min of electrolysis with 1.00 mmol L-1 Fe2+, respectively). The best mineralization achieved in trials of WO2.72 / Vulcan XC72 cathode combined with boron-doped diamond (BDD) anode (82% total organic carbon (TOC) removal of OII by PEF / 1.00 after 3 h and 90% TOC removal of SY by PEF / 050 after 4 h). It was found that SY decolorization was faster and mineralization showed a similar yield independent of oxidized dye.
Keywords: WO2.72 / Vulcan XC72; H2O electrogeneration; decolorization; mineralization; azo dyes